Efficacy of renal preservation: comparative study of Celsior and University of Wisconsin solutions. - Nunes, P (2007)
OBJECTIVE: We sought to compare the efficacy of Celsior and University of Wisconsin (UW) solutions on the perfusion and cold storage of renal grafts for human transplantation. PATIENTS AND METHODS: Retrospective analyses of 313 kidney transplants were performed between 2002 and 2005; group A (n = 160), UW solution and group B (n = 153), Celsior solution were used in the preservation of the organs. The mean donor age was lower in group B (group A = 42.67 years vs group B = 38.96 years; P < .05), living donors were more frequent in the UW group (group A = 10% vs group B = 0.9%; P < .001). Multiorgan procurement procedures were more common in the Celsior group (group A = 75% vs group B = 81.7%; P < .001). Recipients with no associated comorbidities were more frequent in the UW group (group A = 50% vs group B = 36%; P < .001). Recipient mean age, cold ischemia time, and HLA matches were comparable. RESULTS: Delayed graft function (group A = 22.7% vs group B = 20.6%), acute rejections (group A = 21.4% vs group B = 18.4%), and serum creatinine at 6 months (group A = 1.75 vs group B = 1.67 mg/dL), 1 year (group A = 1.47 vs group B = 1.74 mg/dL), and 2 years (group A = 1.43 vs group B = 1.58 mg/dL) showed no differences (P = NS). Graft (group A = 82.23% vs group B = 84.11%) and patient (group A = 93% vs group B = 93.69%) survivals at 3 years were similar (P = NS). There were no differences in the causes of graft loss. CONCLUSION: The efficacy of UW and Celsior solutions is equivalent in the cold storage and renal preservation for transplantation.